On the propagation of plane waves in piezoelectromagnetic monoclinic crystals - Montanaro, A. (Archives of Mechanics, 2015)
In a piezoelectromagnetic crystalline medium belonging to the class 2 of the monoclinic crystallographic system we find some classes of piezoelectricity-induced electromagnetic waves. These are time harmonic plane waves propagating along the symmetry axis and depending only on the axial coordinate. There are two independent modes of propagation, one longitudinal and one transverse, with mechanical and electromagnetical couplings. The transverse mode admits as a particular case an electromagnetic wave with no associated elastic deformation.